Clinical factors before or after device implantation in predicting metal hypersensitivity reactions: A retrospective study. (13th July 2020) - Tam, Idy; Yu, JiaDe; Ko, Lauren N.; Schalock, Peter C.
Abstract: Background: Metal hypersensitivity reactions (MHR) as a cause of implant‐related complications are highly debated and recommendations regarding pre‐procedural allergy evaluation vary dramatically. Objective: To examine patients referred before or after device implantation and identify factors that could be useful to guide the value of patch testing. Methods: Patients who underwent patch testing pre‐ or post‐device implantation between July 2006 and September 2016 were analyzed retrospectively. Results: A series of 127 patients underwent patch testing: pre‐implantation (n = 40) and post‐implantation (n = 87). In the pre‐implant group, a history of metal allergy demonstrated high sensitivity (0.94; 95% CI: 0.83–1.00) and negative likelihood ratio (0.17; 95% CI:0.02–1.29) for diagnosing MHR. No predictive value could be ascribed to any of the clinical symptoms (eg dermatitis, pain, swelling, implant failure, and/or other symptoms) for patients referred following orthopaedic and dental post device implantation. Eight patients in the orthopaedic group and six patients in dental group with relevant patch test reactions underwent implant revisions, and seven and five patients improved, respectively. Conclusions: Pre‐implant patch testing for selected individuals with a history of metal allergy can help guide implant choice. Post‐implant patch testing may be helpful in some patients if other causes have been excluded, as patients with confirmed MHR benefited from revisions.